2011
DOI: 10.1021/ja206513r
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Persistence Length of Amyloid Fibrils Are Correlated to Peptide Molecular Structure

Abstract: The formation of amyloid fibrils is a self-assembly process of peptides or proteins. The superior mechanical properties of these fibrils make them interesting for materials science but constitute a problem in amyloid-related diseases. Amyloid structures tend to be polymorphic, and their structure depends on growth conditions. To understand and control the assembly process, insights into the relation between the mechanical properties and molecular structure are essential. We prepared long, straight as well as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
104
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 40 publications
18
104
3
Order By: Relevance
“…4C and D). These short protofibrillar structures, compatible with the helicoidal ␤-spine observed along the crystal c axis, are often observed in prefibrillar wormlike amyloid oligomers (54,55).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…4C and D). These short protofibrillar structures, compatible with the helicoidal ␤-spine observed along the crystal c axis, are often observed in prefibrillar wormlike amyloid oligomers (54,55).…”
Section: Resultssupporting
confidence: 57%
“…4). Therefore, the ␤-spine arrangement observed in the crystal packing of 2B sol molecules likely reflects the organization adopted by 2B proteins in HAV-infected cells, adding to the growing number of proteins with the ability to self-assemble into functional amyloid-like structures (35,52,55,63,64). Moreover, the ability of the HAV 2B protein to bind microsomal membranes seems to be related to the presence of a putative transmembrane helix located at the C-terminal end of the protein, which is predicted to start 30 residues downstream of the sequence of the present crystallographic structure (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although WPI is a mixture of different proteins, previous studies have shown that PNFs formed under the applied conditions are built from β-lactoglobulin-derived peptides (24). Interestingly, vandenAkker et al demonstrated that pure β-lactoglobulin can assemble into fibrils with different morphology depending on the initial protein concentration (10). In their study, low protein concentration (3%) resulted in long and straight fibrils whereas short, worm-like structures were formed at higher concentrations (7.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the straight fibrils have an apparent height of 4.1 ± 1.1 nm whereas the curved fibrils are thinner (2.5 ± 0.5 nm). Assuming that the straight fibrils are built from 2-3 protofilaments, as described by others (10,25), and that these filaments have the same cross-sectional area as the curved fibrils, we can get an estimate of the relative elastic moduli of the two classes of PNFs. The straight fibrils then appear to have an elastic modulus that is 15-25× higher than the curved fibrils.…”
Section: Resultsmentioning
confidence: 99%
“…This is normally done in PM-IRRAS and SFG by observing the amide bands, which are known to be shifted to higher wavenumbers when the structure changes from β-sheet to α-helices. VandenAkker et al [109] reported changes in secondary structure of amyloid fibrils by following the changes in the amide I band in SFG measurements. Fig.…”
Section: Cell Membrane Modelsmentioning
confidence: 99%